Language quality, content, structure: What analytic ratings tell us about EFL writing skills at upper secondary school level in Germany and Switzerland - Keller, Stefan D.; Lohmann, Julian; Trüb, Ruth; Fleckenstein, Johanna; Meyer, Jennifer; Jansen, Thorben; Möller, Jens (Journal of second language writing, 2024)
Argumentative writing in English as a foreign language (EFL) is an important skill in upper secondary education in Germany and Switzerland. This article provides insights into students’ EFL writing skills in the aspects of language quality, content, and structure (N = 2314 TOEFL argumentative essays from two time-points, beginning and end of Year 11). These essays were analyzed by trained human raters using analytic assessment rubrics for each aspect and evaluated in a cross-sectional as well as a longitudinal perspective. Results show that there were significant variations between these aspects in learners’ texts, suggesting that they represent separate dimensions of the argumentative writing ability. Scores were lowest for language quality, suggesting that this was the most challenging aspect for EFL learners. Learning gains over one year were largest for structure, smaller for content and smallest for language quality. Overall, learners in Switzerland showed higher skills in all three aspects, but German learners showed larger gains in structure over the school year. Implications for classroom learning and further research are discussed.